PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 1 SUTERA - Putra, Dito Hari (Jurnal Edukasi dan Penelitian Matematika, 2025)
The ability to solve mathematical problems is an area of ability that must be developed and mastered in learning mathematics. This ability is in fact still relatively low in class IX SMP Negeri 1 Sutera. Using the Problem Based Learning (PBL) model is one of the efforts that can be made. The research method used is known as quasi-experimental planning. The proficiency test data was analyzed using t-test, and it was concluded that ?-value = 0.000. If ?-value < 0.05, then H0 should be rejected. After comparing the PBL model with the direct learning model in the ninth grade of SMP Negeri 1 Sutera, it is clear that the PBL model provides optimal results.Keywords– Problem Based Learning, Direct Learning, Mathematical Problem-Solving Abilit